The Face of Battle - Keegan, John (London Jonathan Cape Ltd., 1977)
The Face of Battle is military history from the battlefield--a realistic picture of the fears, pressures, and mechanics of fighting a battle, emphasizing three particular campaigns: Agincourt, Waterloo, and the Somme.
Include Illustrations, Bibliography and Index.
Keywords: Battles -- Europe -- Waterloo, Battle of (Belgium : 1815) -- France -- Belgium--Waterloo -- France--Agincourt -- Agincourt, Battle of (France : 1415) -- Somme, 1st Battle of the (France : 1916